Bioinspired microstructures of chitosan hydrogel provide enhanced wear protection. Issue 11 (27th February 2018) - Faivre, Jimmy; Sudre, Guillaume; Montembault, Alexandra; Benayoun, Stéphane; Banquy, Xavier; Delair, Thierry; David, Laurent
Abstract : Hydrogel bilayer structure leads to different tribological behaviors in terms of friction and wear resistance. Abstract : We describe the fabrication of physical chitosan hydrogels exhibiting a layered structure. This bilayered structure, as shown by SEM and confocal microscopy, is composed of a thin dense superficial zone (SZ), covering a deeper zone (DZ) containing microchannels orientated perpendicularly to the SZ. We show that such structure favors diffusion of macromolecules within the hydrogel matrix up to a critical pressure, σ c, above which channels were constricted. Moreover, we found that the SZ provided a higher wear resistance than the DZ which was severely damaged at a pressure equal to the elastic modulus of the gel. The coefficient of friction (CoF) of the SZ remained independent of the applied load with μ SZ = 0.38 ± 0.02, while CoF measured at DZ exhibited two regimes: an initial CoF close to the value found on the SZ, and a CoF that decreased to μ DZ = 0.18 ± 0.01 at pressures higher than the critical pressure σ c . Overall, our results show that internal structuring is a promising avenue in controlling and improving the wear resistance of soft materials such as hydrogels.